WAVELET ANALYSIS OF VARIABILITY OF THE RADIO SOURCE 3C120 IN CENTIMETER WAVELENGTH RANGE - Sukharev, A. L.; Aller, M. F. (Одеські астрономічні публікації, 2014)
3C120 – radio galaxy with an active nucleus has been intensively studied for many years in a wide range of the electromagnetic spectrum. We used observational data for 1966-2010 years, obtained with the radio telescope at Michigan State University (UMRAO) at frequencies of 14.5, 8 and 4.8 GHz. To study the variability of the radio source, we used wavelet method for time series analysis. The main periods in three frequencies are ~4.5 years and 6-12 years (~0.7, 1.6 and 3.4 years for the short-periodic flux component). The delay between radio frequencies was calculated. The comparison between the change in periods of fluctuations of radio fluxes and dynamics of the jet was performed (image VLBI Mojave, 15.4 GHz). Based on the periods found, we conducted forecasting changes in the radio flux and compared the results with the observation data.